2020
DOI: 10.1186/s12885-020-06810-8
|View full text |Cite
|
Sign up to set email alerts
|

Different associations of tumor PIK3CA mutations and clinical outcomes according to aspirin use among women with metastatic hormone receptor positive breast cancer

Abstract: Introduction: The relationships among PIK3CA mutations, medication use and tumor progression remains poorly understood. Aspirin use post-diagnosis may modify components of the PI3K pathway, including AKT and mTOR, and has been associated with lower risk of breast cancer recurrence and mortality. We assessed time to metastasis (TTM) and survival with respect to aspirin use and tumor PIK3CA mutations among women with metastatic breast cancer.Methods: Patients with hormone receptor positive, HER2 negative (HR+/HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…PIK3CA mutation, which leads to increased PI3K activity, is the most common somatic mutation in breast cancer, and 36% of patients with HR+/HER2- breast cancer are PIK3CA mutated ( 196 ). It was suggested that crosstalk between the ER and PI3K/AKT/mTOR signaling pathway exists during breast cancer development ( 197 ).…”
Section: Crosstalk Between Metabolic Regulators and Metastatic Pathwamentioning
confidence: 99%
See 1 more Smart Citation
“…PIK3CA mutation, which leads to increased PI3K activity, is the most common somatic mutation in breast cancer, and 36% of patients with HR+/HER2- breast cancer are PIK3CA mutated ( 196 ). It was suggested that crosstalk between the ER and PI3K/AKT/mTOR signaling pathway exists during breast cancer development ( 197 ).…”
Section: Crosstalk Between Metabolic Regulators and Metastatic Pathwamentioning
confidence: 99%
“…Activation of mTORC1 is adequate to provoke the expression of genes encoding the enzymes of both the oxidative and non-oxidative branches of the PPP, thus activating specific bioenergetic and anabolic cellular processes (194). The PI3K/AKT/mTOR pathway was recently showed to reduce oxidative stress and promote cell survival of breast epithelial cells segregated from the ECM by strengthening flux through the oxidative PPP (195) PIK3CA mutation, which leads to increased PI3K activity, is the most common somatic mutation in breast cancer, and 36% of patients with HR+/HER2-breast cancer are PIK3CA mutated (196). It was suggested that crosstalk between the ER and PI3K/ AKT/mTOR signaling pathway exists during breast cancer development (197).…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Besides, promising data have been observed in randomized phase II trials of AKT inhibitors combined with fulvestrant or paclitaxel in metastatic HR-positive, HER2-negative disease, and Triple-negative breast cancer (TNBC) [27]. A further study has suggested that aspirin can prolong the metastasis time of breast cancer patients with PIK3CA mutation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the mutation of TP53 predicts the poor prognosis for breast cancer [30,31]. The mutation of TP53 leads to the loss of the function of its tumor suppressor gene and leads to malignant expression [28]. Nevertheless, TP53 has not been considered a target for drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PI3KCA mutations in breast cancer occur in 36% of ERα+ HER2- tumors [ 146 ]. Indeed, there is crosstalk between the two pathways, whereby ERα stimulates the PI3K/AKT/mTOR pathway, favoring migration and tumor invasion [ 147 ], and the PI3K/AKT/mTOR pathway activates the expression of ERα [ 148 , 149 ].…”
Section: Metabolic Changes In Tumor Cellsmentioning
confidence: 99%